Adiabatic processes in frequency conversion. Issue 3 (20th October 2013) - Suchowski, Haim; Porat, Gil; Arie, Ady
<x xml:space="preserve">Abstract</x> Adiabatic frequency conversion allowed efficient scalable broadband frequency conversion and was applied successfully to the conversion of ultrashort pulses. The underlying analogy between undepleted pump nonlinear processes and coherently excited quantum systems was extended to multi‐level quantum systems, demonstrating new concepts in frequency conversion. Additionally, the undepleted pump restriction was removed, enabling the exploration of adiabatic processes in the fully nonlinear dynamics regime of nonlinear optics. In this article, the concept of adiabatic frequency conversion is introduced, and recent advances in ultrashort physics, multiprocess systems, and the fully nonlinear dynamics regime are reviewed. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>